Mathematical Literacy Based on Ethnomathematics of Batik Sidoarjo - Janet Trineke Manoy; Mayang Purbaningrum (Didaktik Matematika, 2021)
Mathematical literacy is defined as ones ability to formulate, apply, and interpret mathematics in the real world. Ethnomathematics is a daily mathematical representation or mathematics associated with cultures used to motivate students to learn. This qualitative descriptive aims to describe the mathematical literacy of Year 10 students of Senior High School 1 Sidoarjo in solving ethnomathematics problems related to batik Sidoarjo. Five students were selected using a purposive sampling technique. Data were collected through a mathematical literacy test and interview. The test and interview results were analyzed utilizing a triangulation method proposed by Miles, Huberman, and Saldana. The findings revealed that, in general, Year 10 students of Senior High School 1 Sidoarjo performed adequate mathematical literacy. Teachers need to pay great attention to designing mathematical literacy problems to accustom students to solve mathematical problems in their surroundings.